A strategic plan for Mindanao Land Foundation Inc. - Gordo, Catherine T. (School of Management, University of the Philippines Mindanao, 2011)
The subject of this paper is Mindanao Land Foundation, a development non-government organization operating in Davao City and in some parts of Mindanao for 20 years. It is one of the 297 accredited NGOs by the Philippine Council of NGO Certification. The Foundation primarily assists poor urban and informal communities in the city by building their capacities in the area of negotiation, governance and association/organization management. Generally, the present administration under the leadership of President Aquino is being perceived by many as one of the most civil society organization-friendly government, thus, opening doors for possible partnership opportunities both at the national and local level. The peace and order situation in some parts of Mindanao has also been getting attention from major bilateral and multilateral donor agencies such as the World Bank. In addition, most corporations are now adhering to the concept of corporate social responsibility which can also be explored as partnership opportunity. On the other hand, the inflow of funds to poorer countries (such as Africa) and regions (such as ARMM) can also mean shrinking fund support to development organizations working in the urban sector. There is also a concept in the development work known as ?donor fatigue? especially for donor agencies that have been working in one country for quite a long time. As a general trend, most development organizations are having a hard time in coping with the increasing cash counterpart required by donor agencies, particularly the EU and USAID. Decreasing human resource and workforce in the development work in search for a more secured job can also be perceived as a threat. Given these external conditions, Mindanao Land Foundation was able to position itself as a credible and competent development organization as certified by the PCNC in 2008. It was also able to establish a niche in the area of urban development work particularly in socialized housing. The Foundation also has a vast experience in working with both bilateral and multi-lateral donor agencies either as project implementer or as a consultant. In addition, the Foundation managed to establish long-term partnerships with its partner donor agencies. As a response to the growing counterpart required by donor agencies, the Foundation has invested on possible revenue sources in 2008. The present structure however does not provide a pro-active support to fund-sourcing. There is also a weak institutional support for research and development that would keep current tracks or trends in development work and that would make its work more relevant. Although the Foundation created possible revenue sources, it did not create a separate responsibility unit to manage the profit centre. The Foundation should also look very closely in sorting its accounts properly, specifically the expenses such as that the ideal 20 percent overhead costs is achieved. This ratio of overhead costs vis a vis total project costs is being desired by most donor agencies and is considered as an efficiency measure. One of the proposed strategies is to diversify the fund sources of the Foundation by creating and building new partnership agreements with donor agencies that prioritizes assisting urban poor communities. The Foundation can also look at other potential project partners such as private institutions, corporate foundations and government agencies among others. The Foundation can also look at enhancing its services to include other technical expertise that are more ?fundable? yet are still relevant concerns of the urban poor sector such as disaster risk reduction or climate change adaptation especially in poorer coastal communities. This can be done by scanning possible partnership programs and projects with targeted partner agency followed by series of exploratory talks and discussions and consequent drafting of commonly-agreed proposals. The Foundation can then optimize its planning reviewing and reprogramming (PRR) mechanism as a monitoring tool to keep track of accomplishments and gaps. The quarterly meetings of the project management review committee can include updates on establishing partnership to at least one new donor agency per year. Year-end assessments should also include analyzing annual targets vis a vis actual revenues and subsequent actions to address variances, if any. Given all these, the paper further looked for possible ways on how the Foundation can maximize the opportunities, mitigate the threats, capitalize on its strength and minimize weaknesses by coming up with certain strategies that can ensure its sustainability and relevance in the development arena for the next five years.